Mobilization of imaginaries to build Nordic Indigenous natures. (2nd July 2016) - Maraud, Simon; Guyot, Sylvain
ABSTRACT: This paper is about two Northern territories and peoples, the Sami in the Swedish Lapland and the Cree of James Bay (Quebec, Canada). This comparison aims to show how the North is commonly seen as a human desert – completely wild – and how this imaginative space is full of political and poetic constructions. The colonial vision of the North omits the Indigenous dimension of such territories or includes it as the Ecological Indian of Shepard Krech III. This study shows how what was a patronizing colonial perspective became a tool for the Sami and the Cree to legitimate their involvement in the management of local resources and the protection of nature. Simultaneously, the empowerment of the Indigenous inhabitants of the two Nordic lands – via protected areas such as Laponia or Assinica – is a means of development in the communities. In particular, it supports the emergence of tourism and thus reduces the mental gap between the South and the North and their peoples. Moreover, even when Indigenous tourism is criticized for the promotion of folklore and exoticism, it also enables young generations to reconnect with a culture in oblivion.